Experimental and Mathematical Modelling of Factors Influencing Carbon Dioxide Absorption into the Aqueous Solution of Monoethanolamine and 1-butyl-3-methylimidazolium Dibutylphosphate Using Response Surface Methodology (RSM) - Azhar, F.N.A. (MDPI, 2022)
This paper investigated the solubility of carbon dioxide (CO2 ) in an aqueous solution of monoethanolamine (MEA) and 1-butyl-3-methylimidazolium dibutylphosphate ((BMIM)(DBP)) ionic liquid (IL) hybrid solvents. Aqueous solutions of MEA-(BMIM)(DBP) hybrid solvents containing different concentrations of (BMIM)(DBP) were prepared to exploit the amineâs reactive nature, combined with the ILâs non-volatile nature for CO2 absorption. Response surface methodology (RSM) based on central composite design (CCD) was used to design the CO2 solubility experiments and to investigate the effects of three independent factors on the solubility of CO2 in the aqueous MEA(BMIM)(DBP) hybrid solvent. The three independent factors were the concentration of (BMIM)(DBP) (0â20 wt.), temperature (30â¦Câ60â¦C) and pressure of CO2 (2â30 bar). The experimental data were fitted to a quadratic model with a coefficient of determination (R2 ) value of 0.9791. The accuracy of the developed model was confirmed through additional experiments where the experimental values were found to be within the 95 confidence interval. From the RSM-generated model, the optimum conditions for CO2 absorption in aqueous 30 wt MEA-(BMIM)(DBP) were 20 wt of (BMIM)(DBP), a temperature of 41.1â¦C and a pressure of 30 bar. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.